Final feliz (2018)
Sometimes we do not understand why fairy tales have so much influence on a generation that has their thoughts far beyond their realities. This generation is so afraid of growing up and unable to reach their dreams, they fear the passage of time and want to live at the speed of light. You have so many dreams and imaginary that many times it is not known for sure what the deepest and most sincere longing is. This project seeks to land these dreams, seeks to understand them from a fantastic point of view such as fairy tales and seeks to change fears for expectations. More than to dream is to treasure, is not to forget the way to see the world, not to forget what it is to be young, what makes move the deepest fibers. It is to treasure the lived to impel all that is missing for living...